Yellow Nail Syndrome and Nail Lichen Planus may be Induced by a Common Culprit. Focus on Dental Restorative Substances - Baran, Léon-Robert (Frontiers in Medicine, 2014)
Different clinical appearances such as Yellow nail syndrome and Lichen planus or lichenoid reactions can originate from close or identical etiologies. They may result from dental restorative materials or metal allergy. Interestingly the nail sometimes returns to its normal condition, months after the withdrawal of the offending agents.